Dirty wars [compact disc, unabridged] : the world is a battlefield - Scahill, Jeremy (Blackstone Audio, Inc., 2013)
Jeremy Scahill reveals that President Barack Obama has kept in place many of the most dangerous and secret programs that thrived under his predecessor. Scahill exposes how Obama has escalated these secret US wars and has built up an elite secret US military unit that answers to no one but the president himself. Scahill reveals the existence of previously unreported secret prisons, kidnappings, assassinations, and cover-ups of covert operations gone terribly wrong.